Increased leucocyte apoptosis in transfused β‐thalassaemia patients. (6th December 2012) - Walter, Patrick B.; Porter, John; Evans, Patricia; Kwiatkowski, Janet L.; Neufeld, Ellis J.; Coates, Thomas; Giardina, Patricia J.; Grady, Robert W.; Vichinsky, Elliott; Olivieri, Nancy; Trachtenberg, Felicia; Alberti, Daniele; et al.
Summary This exploratory study assessed apoptosis in peripheral blood leucocytes (PBL) from β‐thalassaemia patients receiving chronic transfusions and chelation therapy (deferasirox or deferoxamine) at baseline, 1, 6, and 12 months. At baseline, thalassaemic PBLs presented 50% greater levels of Bax (BAX), 75% higher caspase‐3/7, 48% higher caspase‐8 and 88% higher caspase‐9 activities and 428% more nucleosomal DNA fragmentation than control subjects. Only neutrophils correlated significantly with apoptotic markers. Previously, we showed that over the treatment year, hepatic iron declined; we now show that the ratio of Bax/Bcl‐2 (BCL2), (−27·3%/year), and caspase‐9 activity (−13·3%/year) declined in both treatment groups, suggesting that chelation decreases body iron and indicators of PBL apoptosis.